Socio-Economic Implications of Covid19 Pandemic to Women Entrepreneurs: A Case of the Informal Sector in Zimbabwe - Chikazhe, lovemore; Mashapure, Rahabhi; Chavhunduka, Desderio; Hamunakwadi, Purity (Business Management and Strategy, 2021)
The purpose of the study was to establish the effect of Covid-19 pandemic to women entrepreneurs in the informal sector of Zimbabwe. A qualitative study was conducted in Mashonaland West province in Zimbabwe. Data was collected through telephone interviews from 16 informal business women entrepreneurs in the retail sector. The participants were involved businesses that include; vegetable vending, operating clothing flea market and cross border trading. The study established that business for women entrepreneurs in the informal sector were affected by inter-province travelling regulations. It was also established that women were most affected as they are responsible for making sure that children are fed on daily basis. To make matters worse, some were widows and others were looking after many orphans. This to a larger extent encouraged cases of strained relationship in the home because of inadequate resources especially food. Cases were also reported of gender-based violence because all members of the family were now spending most of their time together with little resources to use in looking after the family. Thus, health problems such as high blood pressure and were also witnessed. The study recommended the government to provide protective equipment and sanitizers to women entrepreneurs and informal traders so that they can safely continue to produce, distribute and sell their merchandise. The government should assist with transport for smallholder farmers to ferry their produce to markets safely. Also, the government was recommended to communicate with market leaders about how to best handle a lockdown and reopening.